Single ascending dose safety, tolerability, and pharmacokinetic study of econazole in healthy volunteers. Issue 6 (3rd June 2022) - Khera, Himanshi; Pandey, Avaneesh Kumar; Shafiq, Nusrat; Khuller, G.K.; Kondel Bhandari, Ritika; Panditrao, Aditi; Gamad, Nanda; Rohilla, Rachna; Bhattacharjee, Samiksha; Murali, Naveen; cvn, Harish; Belavagi, Devraj; et al.
ABSTRACT: Introduction: Econazole has been found efficacious as antitubercular in in vitro and in vivo animal studies. However, limited information is available for its safety and pharmacokinetics in humans. In our present study we have conducted single ascending dose, safety, and pharmacokinetic evaluation in healthy human volunteers with the purpose of enabling translation for tuberculosis. Methods: This study was conducted as a single-center, ascending-dose, placebo-controlled, double blind design. Three ascending dose were chosen (250 , 500 , and 1000 mg) to be administered as a single oral dose. The volunteers were screened for potential eligibility. Participants were randomized to receive either Econazole or Placebo in a 6:2 design. Safety assessments and pharmacokinetic evaluations were carried out for each cohort. Results: Econazole was found to be safe at all dose levels. No serious or severe adverse events occurred during the study. The AUC (0–∞) showed a response relationship with a value of 49 ± 3.47 h* µg/ml, 17. 86 ± 8.40 hr* µg/ml, 35.54 ± 13.94 hr* µg/ml for 250 mg, 500 mg, and 1000 mg, respectively. Conclusion: Based on the findings of our study, a dose of 500 mg Econazole, once a day orally was considered as appropriate for further evaluation.